Shielding Polysulfide Intermediates by an Organosulfur‐Containing Solid Electrolyte Interphase on the Lithium Anode in Lithium–Sulfur Batteries - Wei, Jun‐Yu; Zhang, Xue‐Qiang; Hou, Li‐Peng; Shi, Peng; Li, Bo‐Quan; Xiao, Ye; Yan, Chong; Yuan, Hong; Huang, Jia‐Qi (Advanced materials (Weinheim), 2020)
The lithium–sulfur (Li–S) battery is regarded as a promising high‐energy‐density battery system, in which the dissolution–precipitation redox reactions of the S cathode are critical. However, soluble Li polysulfides (LiPSs), as the indispensable intermediates, easily diffuse to the Li anode and react with the Li metal severely, thus depleting the active materials and inducing the rapid failure of the battery, especially under practical conditions. Herein, an organosulfur‐containing solid electrolyte interphase (SEI) is tailored for the stabilizaiton of the Li anode in Li–S batteries by employing 3,5‐bis(trifluoromethyl)thiophenol as an electrolyte additive. The organosulfur‐containing SEI protects the Li anode from the detrimental reactions with LiPSs and decreases its corrosion. Under practical conditions with a high‐loading S cathode (4.5 mgS cm−2), a low electrolyte/S ratio (5.0 µL mgS−1), and an ultrathin Li anode (50 µm), a Li–S battery delivers 82 cycles with an organosulfur‐containing SEI in comparison to 42 cycles with a routine SEI. This work provokes the vital insights into the role of the organic components of SEI in the protection of the Li anode in practical Li–S batteries. An organosulfur‐containing solid electrolyte interphase (SEI) is tailored for the stabilization of the Li anode in Li–S batteries by employing 3,5‐bis(trifluoromethyl)thiophenol as an electrolyte additive. The organosulfur‐containing SEI protects the Li anode from the detrimental reactions with Li polysulfides (LiPSs). A Li–S battery delivers 82 cycles with an organosulfur‐containing SEI in comparison to 42 cycles with a routine SEI under practical conditions.